Inferred metagenomic comparison of mucosal and fecal microbiota from individuals undergoing routine screening colonoscopy reveals similar differences observed during active inflammation - Tang, Mei San; Poles, Jordan; Leung, Jacqueline M.; Wolff, Martin J.; Davenport, Michael; Lee, Soo Ching; Lim, Yvonne Ai Lian; Chua, Kek Heng; Loke, P'ng; Cho, Ilseung (Taylor & Francis, 2015)
The mucosal microbiota lives in close proximity with the intestinal epithelium and may interact more directly with the host immune system than the luminal/fecal bacteria. The availability of nutrients in the mucus layer of the epithelium is also very different from the gut lumen environment. Inferred metagenomic analysis for microbial function of the mucosal microbiota is possible by PICRUSt. We recently found that by using this approach, actively inflamed tissue of ulcerative colitis (UC) patients have mucosal communities enriched for genes involved in lipid and amino acid metabolism, and reduced for carbohydrate and nucleotide metabolism. Here, we find that the same bacterial taxa (e.g. Acinetobacter) and predicted microbial pathways enriched in actively inflamed colitis tissue are also enriched in the mucosa of subjects undergoing routine screening colonoscopies, when compared with paired samples of luminal/fecal bacteria. These results suggest that the mucosa of healthy individuals may be a reservoir of aerotolerant microbial communities expanded during colitis.